Christmas [compact disc] : live from Phoenix (Fervent Records/Curb Records : Word Entertainment, 2017)
For King & Country's Christmas: Live in Phoenix is a collection of 10 Christmas originals, re-imagined classics, as well as a special version of their hit song 'The Proof Of Your Love' featuring their sister and artist Rebecca St. James. This album released in late 2017 was recorded on the final night of the band's 15-date arena Christmas tour in December 2016 at the Grand Canyon University Arena in Phoenix, AZ.